Social Workers´ Reflections on Forced Migration and Cultural Diversity - Towards Anti-Oppressive Expertise in Child and Family Social Work - Anis Merja; Turtiainen Kati (MDPI, 2025)
Social work in Finland, like in many other countries, has faced various challenges after the large scale of forced migration in 2015. Although working with migrants is not a new area in social work, the exceptionally large amount of asylum seekers in the Finnish society caused a need for improved social work expertise. Our article deals with Finnish social work practitioners’ reflections on multicultural, multilingual and transnational issues with a client group, which is in a vulnerable situation after forced or other forms of migration. The practitioners participating in our study have either attended a specializing education of child, youth and family social work or taken part in peer group discussions in order to develop multicultural expertise. All attendants worked in child and family social work during the study periods in the years 2018–2020. Applying a qualitative methodology by using thematic analysis, we analyze the social workers’ texts and discussions in order to find out the challenges and possibilities as well as needs and tools towards anti-oppressive practice in social work. The identified challenges are connected to differentiated local services, social workers’ uncertainty of their expertise in working with forced migrants, nationally defined welfare services and communication skills in client encounters. Some ways ahead were recognized in structural social work and further education to improve knowledge and skills. Social workers emphasize the need for self-reflection on their prejudices and in developing anti-oppressive practices, which contain human rights aspects and client-oriented practices. Specializing education and reflective group discussion gave a platform to social workers for reflective professional discussions and writings, which seem to have broadened their expertise in multicultural social work.